2013
DOI: 10.1063/1.4825276
|View full text |Cite
|
Sign up to set email alerts
|

Complex structural dynamics of bismuth under laser-driven compression

Abstract: With the aid of nanosecond time-resolved X-ray diffraction techniques, we have explored the complex structural dynamics of bismuth under laser-driven compression. The results demonstrate that shocked bismuth undergoes a series of structural transformations involving four solid structures: the Bi-I, Bi-II, Bi-III and Bi-V phases. The transformation from the Bi-I phase to the Bi-V phase occurs within 4 ns under shock compression at ~11 GPa, showing no transient phases with the available experimental conditions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
2
16
1
Order By: Relevance
“…To avoid this we have chosen to study melting in Bi on shock release from the high-pressure Bi-V phase. Such a study also allows a direct comparison with the recent diffraction study of Bi by Hu et al, which reported several solid-solid transitions on release on nanosecond timescales [12]. Here we present femtosecond X-ray diffraction measurements of Bi that provide definitive evidence of liquid diffraction, and which show that on release Bi-V melts within 3 ns at P-T conditions that are in excellent agreement with the equilibrium melt curve [14].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…To avoid this we have chosen to study melting in Bi on shock release from the high-pressure Bi-V phase. Such a study also allows a direct comparison with the recent diffraction study of Bi by Hu et al, which reported several solid-solid transitions on release on nanosecond timescales [12]. Here we present femtosecond X-ray diffraction measurements of Bi that provide definitive evidence of liquid diffraction, and which show that on release Bi-V melts within 3 ns at P-T conditions that are in excellent agreement with the equilibrium melt curve [14].…”
supporting
confidence: 80%
“…However, by directly determining all of the phases present in our samples using 80 fs X-ray exposures, our data show unequivocally that Bi melts within 3 ns on release from Bi-V. We note that a recent diffraction study of the solid-solid phase transitions in Bi on shock release from lower pressures [12], using 100 ps X-ray exposures, found three successive phase transitions -Bi-V → Bi-III → Bi-II → Bi-I -to occur within 30 ns, with individual transition times similar to the melting time reported here. Ultrafast X-ray diffraction is thus an excellent way of unambiguously determining both the nature and timescale of shock-induced phase transitions on the nanosecond timescales of laser compression experiments.…”
Section: D Diffraction Images Were Recorded On Cspad De-mentioning
confidence: 50%
See 1 more Smart Citation
“…Luo et al, 2012;Hu et al, 2013;Chen et al, 2014;Eakins & Chapman, 2014;Rack et al, 2014;Kantor et al, 2014;Kareh et al, 2014;Karagadde et al, 2015;Jensen et al, 2015; and references therein) have began to exploit synchrotron radiation to provide some of the first observations of important damage mechanisms at the mesoscale. Radiographic studies report observations of the early stages of buried pore collapse (Eakins & Chapman, 2014), crack pattern formation and instability growth (Luo et al, 2012;Jensen et al, 2015), while diffraction experiments have identified remarkably complex phase behaviour in bismuth (Hu et al, 2013). 1 However, several authors highlight the challenges associated with bringing dynamic experiments to synchrotron environments, noting trade-offs between signal-to-noise ratio (SNR), time resolution, interframe time and image ghosting (Luo et al, 2012;Eakins & Chapman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The plasma confined target consisted of a backup plastic film (25 µm thick), an Al foil (3 µm thick), and the sample. The sample was a 20 µm thick foil of polycrystalline bismuth (99.97% pure) obtained from Goodfellow Cambridge Limited (Huntingdon, UK) [19]. A laser pulse with energy of 1.0 J and pulse width of 8 ns was focused on the target with a spot diameter of 0.48 mm.…”
Section: Phase Transition Dynamics In Polycrystalline Bismuthmentioning
confidence: 99%